The Errors of Atheism. By J. Angelo Corlett - Mawson, T. J. (The journal of theological studies, 2011)
In most philosophical debates concerning classical theism, the vast majority of the disputants may be divided into two camps: those who believe we have more reason to suppose such a theism true than we have to suppose it false and those who believe we have more reason to suppose it false than we have to suppose it true. The former are usually labelled ‘theists’ and the latter ‘atheists’. The position that in fact the reasons in favour of and against theism are exactly balanced (perhaps because there are none, either way) is hardly ever occupied and thus ‘agnosticism’, if that’s the best name for that view (which it probably isn’t), is rather underexplored. The blurb on the back of The Errors of Atheism might lead one to expect that such an exploration will be found within its covers.